The genetics underlying acquired long QT syndrome: impact for genetic screening. (28th December 2015) - Itoh, Hideki; Crotti, Lia; Aiba, Takeshi; Spazzolini, Carla; Denjoy, Isabelle; Fressart, Véronique; Hayashi, Kenshi; Nakajima, Tadashi; Ohno, Seiko; Makiyama, Takeru; Wu, Jie; Hasegawa, Kanae; et al.
Abstract: Aims: Acquired long QT syndrome (aLQTS) exhibits QT prolongation and Torsades de Pointes ventricular tachycardia triggered by drugs, hypokalaemia, or bradycardia. Sometimes, QTc remains prolonged despite elimination of triggers, suggesting the presence of an underlying genetic substrate. In aLQTS subjects, we assessed the prevalence of mutations in major LQTS genes and their probability of being carriers of a disease-causing genetic variant based on clinical factors. Methods and results: We screened for the five major LQTS genes among 188 aLQTS probands (55 ± 20 years, 140 females) from Japan, France, and Italy. Based on control QTc (without triggers), subjects were designated 'true aLQTS' (QTc within normal limits) or 'unmasked cLQTS' (all others) and compared for QTc and genetics with 2379 members of 1010 genotyped congenital long QT syndrome (cLQTS) families. Cardiac symptoms were present in 86% of aLQTS subjects. Control QTc of aLQTS was 453 ± 39 ms, shorter than in cLQTS (478 ± 46 ms, P < 0.001) and longer than in non-carriers (406 ± 26 ms, P < 0.001). In 53 (28%) aLQTS subjects, 47 disease-causing mutations were identified. Compared with cLQTS, in 'true aLQTS', KCNQ1 mutations were much less frequent than KCNH2 (20% [95% CI 7–41%] vs. 64% [95% CI 43–82%], P < 0.01). A clinical score based on control QTc, age, and symptoms allowed identification of patients more likely to carry LQTS mutations. Conclusion: A third of aLQTS patients carry cLQTS mutations, those on KCNH2 being more common. The probability of being a carrier of cLQTS disease-causing mutations can be predicted by simple clinical parameters, thus allowing possibly cost-effective genetic testing leading to cascade screening for identification of additional at-risk family members.